2020
DOI: 10.1213/ane.0000000000003757
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Model for Identifying Cardiac Side Effects of Anesthetics

Abstract: The understanding of anesthetic side effects on the heart has been hindered by the lack of sophisticated clinical models. Using micropatterned human-induced pluripotent stem cell-derived cardiomyocytes, we obtained cardiac muscle depressant profiles for propofol, etomidate, and our newly identified anesthetic compound KSEB01-S2. Propofol was the strongest depressant among the 3 compounds tested, exhibiting the largest decrease in contraction velocity, depression rate, and beating frequency. Interestingly, KSEB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…To verify the effect of these CHMs on DMD cardiomyocyte function, we used DMD hiPSC-CMs. To detected the effect of CHM herbs on single cardiomyocyte contraction, hiPSC-CMs were grown into rod-shape single cells using microprinting ( Chang et al, 2020 ). Micropatterned hiPSC-CMs exhibited well-aligned sarcomere structures after 3 days ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the effect of these CHMs on DMD cardiomyocyte function, we used DMD hiPSC-CMs. To detected the effect of CHM herbs on single cardiomyocyte contraction, hiPSC-CMs were grown into rod-shape single cells using microprinting ( Chang et al, 2020 ). Micropatterned hiPSC-CMs exhibited well-aligned sarcomere structures after 3 days ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Single hiPSC-CMs were seeded on micropatterns 3 days prior to assay as previously described ( Chang et al, 2020 ). Analysis of spontaneous beating of hiPSC-CMs was performed using video microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Micropatterning ridges or protein substrates on culture vessels have been shown to benefit CM function and maturity and cardiomyogenic differentiation potential (McCain et al, 2013). This was clearly reflected in a relevant disease phenotype observed in a model of Barth syndrome using TAZ mutant patient lines (Wang et al, 2014) and drug responses (Chang et al, 2018).…”
Section: Reverse Engineering Heart Physiologymentioning
confidence: 99%
“…Therefore, other, new, hypnotics are needed. To test one such new compound KSEB01‐S2 (a potent GABA A receptor ligand), investigators used patient‐derived iPSC‐CMs and demonstrated that KSEB01‐S2 reduced cardiomyocyte function less than propofol (Chang et al, 2020). These data acquired in human tissue are important to pave the way towards future clinical testing.…”
Section: Using Ipsc Technology To Evaluate Anaesthetic Agents In Cardmentioning
confidence: 99%
“…These examples illustrate how iPSC can be used to identify patient‐specific variance resulting in clinical phenotypes. In addition, patient‐specific iPSC derivatives can be exposed to a range of drugs to detect drug–drug and/or drug–gene interactions (Lau, Paik, & Wu, 2019), test new anaesthetic compounds (Chang et al, 2020), complement gene‐editing strategies (Christidi, Huang, & Brunham, 2018), and discover new potential drug targets (Paik, Chandy, & Wu, 2020) (Figure 1). Multiple commercially produced human iPSC‐CM and iPSC‐NC lines are currently available (Table 1).…”
Section: Introductionmentioning
confidence: 99%